Control of Fusarium graminearum in Wheat With Mustard-Based Botanicals: From in vitro to in planta - Drakopoulos, Dimitrios; Meca, Giuseppe; Torrijos, Raquel; Marty, Anja; Kägi, Andreas; Jenny, Eveline; Forrer, Hans-Rudolf; Six, Johan; Vogelgsang, Susanne (Frontiers in Microbiology, 2020)
Fusarium graminearum is a phytopathogenic fungus that causes Fusarium head blight in small-grain cereals, such as wheat, with significant yield reductions. Moreover, it contaminates the cereal grains with health-threatening mycotoxins, such as deoxynivalenol (DON), jeopardizing food and feed safety. Plant-based biopesticides, i.e. botanicals, have recently gained increased interest in crop protection as alternatives to synthetic chemical products. The main objective of this study was to test the control efficacy of botanicals based on white or Indian/oriental mustard seed flours (Tillecur - Ti, Pure Yellow Mustard - PYM, Pure Oriental Mustard - POM, Oriental Mustard Bran - OMB) on F. graminearum infection and mycotoxin accumulation in wheat grain. Botanicals at 2 % concentration showed a higher efficacy in inhibiting mycelium growth in vitro compared with a prothioconazole fungicide (F). In the growth chamber experiment under controlled conditions, the spraying agents reduced DON content in grain in the following order: F = Ti = PYM > POM > OMB. The antifungal activity of the botanicals may be attributed to their bioactive matrices containing isothiocyanates (ITCs) and phenolic acids. Allyl ITC was detected in POM and OMB at 8.38 and 4.48 mg g-1, while p-hydroxybenzyl ITC was found in Ti and PYM at 2.56 and 2.44 mg g-1, respectively. Considerable amounts of various phenolic acids were detected in all botanicals. Under field conditions, only the use of F significantly decreased F. graminearum infection and DON content in grain. An additional important finding of this study is that disease control was more difficult when infection was done with ascospores than conidia, which might have several potential implications considering that ascospores are more important in Fusarium head blight epidemics. Our results suggest that mustard-based botanicals are promising biopesticides for the control of Fusarium head blight in small-grain cereals, but for field applications, an appropriate formulation is necessary to stabilize and prolong the antifungal activity, especially against ascospores.